NON-TRADITIONAL EDUCATIONAL TECHNOLOGIES USED IN EDUCATION - Rayimova Nigina Bobo-nazarovna (American Journals, 2024)
In this article, non-traditional educational technologies used in education, elements that make up the educational process, specific features of non-traditional educational technologies, the development of the student's independent thinking skills, educational - focus on providing the educational process with new pedagogical technologies, collaborative learning technology, modelling technology, research or project technology are highlighted.
Keywords: Education, educational process, knowledge, student, teacher, educational process, educational technology, design.